RAREST BUCKETFUL PURE DROWNING ADULT FEMALE HOMICIDE BY JILTED LAWYER LOVER (Journal of Forensic Medicine & Toxicology, 2018)
Bathtub fatalities are relatively rare to involve unattended young children. Majority masqueraded as accidents but few are undoubtedly homicides in both children and adults. Rarest homicidal drowning of middle aged female deserted by husband is reported. Perpetrator paramour lawyer inebriated victim to drag to bathroom and death drowned by submerging her mouth and nose in bucketful of water. He placed another water filled bucket over her shoulder ensuring continued airway submersion under water. Tap and water air cooler were left running to delay crime detection. Role of crime scene, evidence preservation and criminal psychology is emphasized to elucidate death manner in this unprecedented case of bucket related pure drowning homicide.
Keywords: Pure drowning homicide; Bathtub homicides; Diatom fingerprinting